The dragoman renaissance - Rothman, Ella Natalie, 1976- (Ithaca ; London)
xxiii, 419 sayfa
Keywords: “This book studies the role of dragomans (diplomatic interpreter-translators) in mediating ethno-linguistic, political, and religious relations between the Ottoman Empire and its European neighbors from ca. 1550 to ca. 1730. It considers both their Istanbul-centered social lives, and how the dictionaries, reports, and visual representations they created were central to the production of Europeanist knowledge about the Ottoman world“--